TEST CHARACTERISTICS OF CENTRIFUGAL PUMPS ON COOLING HYDRONIC SYSTEM USING ENVIRONMENTAL FRIENDLY REFRIGERATION - Yudhy Kurniawan; Kusnandar Kusnandar (Jurnal Teknologi Terapan, 2018)
In generally cooling hydronic system applied to large-scale commercial or industrial use, where water cooling is processed through heat transfer mechanism in the evaporator pipe using a vapour compression system such as a chiller with refrigerant. The research idea is based on not available practice test of cooling hydronic system at the Department of Refrigeration and Air Conditioning Engineering at State Polytechnic of Indramayu which is the main competency in the course of Air Conditioning Applied. As teh utilization practice made cooling hydronic system by utilizing a vapour compression system that is split AC using refrijeran R32 is environmentally friendly. The split AC system modifies its evaporator coil into a heat exchange medium to cool water in the water tank. The cold water is then distributed in the piping installation system with the two pumps that are varied in series and parallel. From this process, it is necessary to know the working capability of the pumps in terms of its characteristics (head and capacity) or its performance, including energy losses and cooling capacity system. The results obtained are analyzed and the calculation is in accordance with theoretically known study.